Characterization of rumen, fecal, and milk microbiota in lactating dairy cows - Williamson, Jenna R.; Callaway, Todd R.; Lourenco, Jeferson M.; Ryman, Valerie E. (Frontiers in Microbiology, 2022)
Investigations of the gastrointestinal microbiome have shown potential for improvement of feed efficiency and reduction of production costs through targeting rumen and fecal microbiota. However little progress has been made in manipulation of the gut microbiomes in dairy cattle to improve milk yield and milk quality. Even less understood is the milk microbiome, which may be critically important to dairy production. Understanding the milk microbiome may provide insight into how the microbiota correlate with milk yield and milk quality. The objective of this study was to characterize similarities between rumen, fecal, and milk microbiota simultaneously, and to investigate associations between microbiota, milk somatic cell count (SCC), and milk yield. A total of 51 mid-lactation, multiparous Holstein dairy cattle were chosen for sampling of ruminal, fecal, and milk contents that were processed for microbial DNA extraction and sequencing. Cows were categorized based on low, medium, and high SCC; as well as low, medium, and high milk yield. Beta diversity indicated that ruminal, fecal, and milk populations were distinct (P < 0.001). Additionally, the Shannon index demonstrated that ruminal microbial populations were more diverse (P < 0.05) than were fecal and milk populations, and milk microbiota was the least diverse of all sample types (P < 0.001). While diversity indices were not linked (P > 0.1) with milk yield, milk microbial populations from cows with low SCC demonstrated a more evenly distributed microbiome in comparison to cows with high SCC values (P = 0.053). Ultimately, further investigation is needed to determine linkages between the microbiota of the gastrointestinal tract and the milk/mammary gland that may lead to strategies to improve mammary health and milk quality through microbial population manipulation.